2011
DOI: 10.1186/1753-2000-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone in the treatment of conduct disorder in preschool children without intellectual disability

Abstract: BackgroundThe DSM-IV-TR (Diagnostic and Statistical Manual of Mental Disorders, 4th edition Textrevision) highlights the especially poor outcomes of early-onset conduct disorder (CD). The strong link between the patient's age at treatment and its efficacy points the importance of early intervention. Risperidone is one of the most commonly studied medications used to treat CD in children and adolescents. The aim of this study is to obtain preliminary data about the efficacy and tolerability of risperidone treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Also our study is in agreement with Ercan's study about risperidone effects for the treatment of normally developing preschool children with diagnosis of Conduct Disorder (CD) co-morbid with ADHD. Result of this open label trial shows that risperidone significantly improved symptoms and subscales of symptoms such as inattention subscale score ( 28 ). Although we used a different questionnaire, in our study there was significant improvement based on Conners scale that measures CD, ODD, ADHD as well as other symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also our study is in agreement with Ercan's study about risperidone effects for the treatment of normally developing preschool children with diagnosis of Conduct Disorder (CD) co-morbid with ADHD. Result of this open label trial shows that risperidone significantly improved symptoms and subscales of symptoms such as inattention subscale score ( 28 ). Although we used a different questionnaire, in our study there was significant improvement based on Conners scale that measures CD, ODD, ADHD as well as other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ercan et al measured symptoms with Turgay DSM-IV Based Disruptive Behavior Disorders Child and Adolescent Screening and Rating Scale that assesses inattention, hyperactivity-impulsivity, opposition-defiance and conduct disorder. Indeed both questionnaires assess same symptoms ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ülkemizde yapılan bir çalışmada, normal gelişim özellikleri gösteren DEHB+DB tanılı 8 okul öncesi yaşta çocukta risperidon tedavisinin etkinliği 8 haftalık açık çalışmada değerlendirilmiştir. Tüm olgular risperidon tedavisine iyi veya çok iyi yanıt vermiş olup, ciddi bir yan etki gözlenmemiştir (33) . Bu yazın bilgileri ile tutarlı olarak eştanı olmayan ve 1 eştanısı olan hastaların psikososyal yaklaşımların tedavide önerildiği, ancak 2 eştanısı olan hastalarda ilaç tedavisinin başlandığı belirlenmiştir.…”
Section: Discussionunclassified
“…Risperidone is certainly being used in a variety of childhood psychiatric illnesses at young ages. A recent report in a small cohort of patients with conduct disorder (mean age 42 months) treated with risperidone at a mean dosage of 0.78mg/day and a maximum of 1.5mg/day (Ercan et al, 2011) found substantial increase in prolactin from a baseline mean of 5.3 ng/ml to 70 ng/ml at 8 weeks. Six of the eight children who completed the study had hyperprolactinaemia without clinical symptoms, as stated by the authors.…”
Section: Hyperprolactinaemia In Children and Adolescentsmentioning
confidence: 95%